PENGARUH PENGETAHUAN, SIKAP DAN MOTIVASI MASYARAKAT TERHADAP PERILAKU PENGGUNAAN DETERGEN - Tang, Muh.; Dirawan, Gufran D. (Pascasarjana Universitas Negeri Makassar, 2023)
The research objective was to determine the influence of knowledge, attitudes, and motivation on detergent use behavior. Detergent waste water is one of the biggest contributors to environmental pollution. This study used a questionnaire data collection method to the community totaling 60 people and carried out multiple regression analysis. The results of this research show that: (i) the influence of knowledge on detergent usage behavior is included in the high category. (ii) the effect of attitudes towards detergent use behavior is in the high category, (iii) the effect of motivation on detergent use behavior is included in the high category, and (iv) the effect of knowledge, attitudes, and motivation on detergent use behavior shows a significant regress equation. This means that the community influences the behavior of using detergent with regression coefficients of 0.043, 0.010 and 0.000 respectively.